Sydney Basin in the Triassic–a review of the geology, flora and fauna, and ecosystems. The Wianamatta Group - Graham McLean (Records of the Australian Museum, 2025)
As the town of Sydney grew in the 1800’s the search for building material and the later construction of railways in the colony revealed an extensive trove of Triassic fossils. Many were passed to and held in scientific collections to later be described. The Australian Museum was one of the institutions which progressively built an extensive and diverse collection of this material. Drawing primarily on these resources, this study reviewed all known flora and fauna of the Middle Triassic Wianamatta Group of the Sydney Basin. Each taxon is illustrated, and a brief taxonomic history is included. To allow efficient access to specimens, museum registration numbers are listed and specimens’ positions in the collection noted. The range of the known biodiversity encompasses three temnospondyls, twelve fishes, fourteen insects, five crustaceans, two molluscs and two plants recovered from different sites across the basin. In some cases, this study also includes specimens and images from the Geological Survey of New South Wales, the Queensland Museum and the Natural History Museum, London. To place the collection in context, particularly for educators working with students, a brief geological description and inferred ecosystems of the Wianamatta Group are included.